Implementation of Financial Compensation Based on National Policy and Its Impact on Primary School Teachers' Performance: A Literature Review - Warsih Warsih; Muhammad Sholeh; Ayu Wulandari (International Journal of Education, Language, and Religion, 2025)
This literature review comprehensively examines the implementation of financial compensation policies for primary school teachers in Indonesia and their impact on teacher performance. The analysis focuses on national policies related to teacher compensation, the implementation process in different regions, and an evaluation of their effectiveness in improving teacher performance. The review integrates findings from various studies over the period 2010-2023, with a particular focus on the teacher certification and professional allowance programs. The results of the review show that despite a general improvement in teacher welfare, policy implementation still faces challenges such as inequitable distribution, delays in disbursement, and unmet qualifications. The impact on teacher performance shows varying results with improvements in aspects of welfare and motivation, but does not always correlate linearly with improvements in pedagogical competence and student learning achievement. Recommendations are given for improving the compensation system, improving monitoring and evaluation mechanisms, and developing a more comprehensive performance-based compensation model.